Time-Restricted Feeding a High-fat Diet in Mice Elevates Plasma Concentration of Saturated Fatty Acids but Reduces Concentrations of Multiple Amino Acids (OR27-02-19). (13th June 2019) - Rust, Bret; Mehus, Aaron; Idso, Joseph; Picklo, Matthew
Abstract: Objectives: Obesity and obesity-related disease contribute to health care costs and pose serious health risks. Rodent studies indicate that time-restricted feeding (TRF) may be effective in reducing adiposity and metabolic disease associated with obesity. However, the metabolic pathways impacted by TRF in the context of obesogenic, high-fat (HF) diets need clarity. In the present work we examined the metabolomic changes in plasma induced by TRF of a HF diet in mice compared to a HF diet eaten ad libitum (AL) vs AL intake of a low-fat (LF) control diet. Methods: Male mice (12 weeks old) were fed a LF-AL diet (16%en fat), a HF-AL diet (48%en fat) or a HF diet restricted to feeding for 12 hours per day during the dark phase (HF-TRF). In week 9 of the study, energy expenditure data were collected. After 12 weeks, animals were fasted and plasma collected for clinical chemistries and metabolomic analysis. Multivariate analysis was used to discriminate diet treatments in untargeted metabolomic data. Results: Energy expenditure measurements throughout the day showed a markedly reduced fasting respiratory exchange ratio (RER) in HF-TRF mice during the inactive (light) phase compared to AL groups. Measures of insulin resistance, while increased with HF-AL intake, were resolved in the HF-TRF group. Partial least squares discriminant analysis revealed plasma non-esterified fatty acids (NEFA) and amino acids (AA) to be important discriminators between diet treatments. TRF resulted in elevated NEFA concentrations of the saturated fatty acids (12:0 to 18:0) and the polyunsaturated fatty acids α-linolenic acid and linoleic acid compared to HF-AL. Conversely, the concentrations of aromatic and branched chain amino acids were reduced in HF-TRF mice compared to HF-AL mice. Conclusions: Alterations in plasma metabolites following TRF of a HF diet are consistent with greater lipid utilization during the inactive phase as reflected in the RER. Decreases in the aromatic and branched chain amino acid concentrations are consistent with improved insulin sensitivity in humans. Funding Sources: This work was supported by USDA-ARS project 3062-51000-053-00D. Supporting Tables, Images and/or Graphs: